2D vs. 3D cell culture systems - Bindal, Ishita. (2010)
Three-dimensional cell cultures are known to have several advantages over two-dimensional cell cultures, including the ability to mimic in vivo environments, demonstrate structure-function relationships, give structural support for tissue engineering constructs and provide a platform to understand cell interactions with the environment. However the feasibility and efficiency of a three-dimensional cell culture system is still questionable. Therefore, this study focuses on the characterization of HEL cell growth in two-dimensional versus three-dimensional cultures. For two dimensional cell cultures, cells were suspended directly in the medium which was contained in 96 well plates and for three dimensional cell cultures cells were first suspended in alginate hydrogels which were immersed in the medium also contained in the 96 well plate. The proliferation rate of the cells were monitored over a period of ten days to study the optimum seeding densities for both two-dimensional and three-dimensional cell cultures. Further studies were also done to deduce the ideal hydrogel size and hydrogel composition, i.e. gelatin to alginate ratio in which cell proliferation would be the highest. It was concluded that three-dimensional cell cultures are indeed more practical than two dimensional cell cultures as they allow cells to proliferate for a longer duration of time. Moreover, alginate hydrogels proved to be an ideal environment for cell proliferation. In alginate hydrogels, the ideal seeding density is 2x105cell/ml as this resulted in the shortest lag phase and fastest growth in cell numbers. Also, larger hydrogels were seen to be more favourable for higher proliferation rates and a greater percentage of gelatin in the hydrogel composition allowed hydrogels to expand more, thereby making more space and allowing for more number of cells to co-exist. However, there is a limit to how large the hydrogel should be as after a certain point, the nutrient accessibility of cells seeded in the core is very low. In addition to that, adding more gelatin also compromises the integrity of the hydrogel as it is more easily damaged.